2019
DOI: 10.25115/eea.v36i2.2540
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fair Value Measurement in Financial Reporting: A Literature Review

Abstract: Desde hace unos cuarenta años, el valor razonable se ha venido utilizando cada vez más en las normas emitidas por el IASB y por el FASB. En este sentido, ha existido un gran debate con relación a la relevancia y a la fiabilidad del valor razonable como método de valoración. En principio, los marcos conceptuales del IASB y del FASB se basan en el Paradigma de la Utilidad, y el valor razonable debería aplicarse si ofrece información relevante a los inversores. En el presente artículo revisamos las investigacione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Thus, in the case of investment properties, there is a great discrepancy in the existing literature. On one hand, those who consider greater relevance of fair value versus historical cost (Allen & Ramanna, 2013;Baboukardos & Rimmel, 2014;Barth, 2014;Ehalaiye et al, 2017;Magnan, 2009;Zamora-Ramirez & Morales-Díaz, 2018); on the other, the position in favour of historical cost (Acaranupong, 2017;Liao, 2013;Machado & Machado, 2013;Magnan, 2009;Müller et al, 2015;Siam & Abdullatif, 2011). Other studies have found no empirical evidence that the fair value model increases the explanatory power of the price based on financial information (Hassan et al, 2006;Machado & Machado, 2013;McInnis et al, 2018), or they show mixed evidence (Danbolt & Rees, 2008;Hitz, 2007;Koonce et al, 2011;Sellhorn & Stier, 2019).…”
Section: Theoretical Framework and Development Of Hypothesismentioning
confidence: 99%
“…Thus, in the case of investment properties, there is a great discrepancy in the existing literature. On one hand, those who consider greater relevance of fair value versus historical cost (Allen & Ramanna, 2013;Baboukardos & Rimmel, 2014;Barth, 2014;Ehalaiye et al, 2017;Magnan, 2009;Zamora-Ramirez & Morales-Díaz, 2018); on the other, the position in favour of historical cost (Acaranupong, 2017;Liao, 2013;Machado & Machado, 2013;Magnan, 2009;Müller et al, 2015;Siam & Abdullatif, 2011). Other studies have found no empirical evidence that the fair value model increases the explanatory power of the price based on financial information (Hassan et al, 2006;Machado & Machado, 2013;McInnis et al, 2018), or they show mixed evidence (Danbolt & Rees, 2008;Hitz, 2007;Koonce et al, 2011;Sellhorn & Stier, 2019).…”
Section: Theoretical Framework and Development Of Hypothesismentioning
confidence: 99%
“…These standards are based on a mixed measurement model under which historical cost coexists with fair value. Certain elements are measured at historical cost while others are measured at fair value (Cairns, 2006;Zamora-Ramírez and Morales-Díaz, 2018). In financial instruments 4 area, financial assets and liabilities are classified in several categories.…”
Section: Introductionmentioning
confidence: 99%
“…According to other, German GAAP standards are not worse (Van Tendello and Vanstraelen, 2005). Next theme of fair value, which is currently one of the most widely used measurement methodologies in IFRS1 accounting standards (Zamora-Ramirez and Morales-Diaz, 2018).Other authors have argued that IFRS are intended for consolidated accounts and for the needs of capital market investors, raising practical concerns about the relevance of IFRS for separate financial statements (European Financial Reporting Advisory Group, 2011) (Palea, 2014). Many authors, in turn, argued that the lower importance of the unitary financial statements may stem from their use for regulatory and tax purposes (Choi and Mueller, 1992;Delvaille et.al., 2005;Whittington, 2005).…”
mentioning
confidence: 99%